Alumina fiber reinforced mullite ceramic-based composite material with volume concentration gradient and preparation method of alumina fiber reinforced mullite ceramic-based composite material

By introducing a volume concentration gradient distribution structure into the alumina fiber reinforced mullite ceramic matrix composite, the shortcomings of existing materials in thermal insulation performance are solved, and efficient improvement of thermal insulation performance and coordinated improvement of mechanical properties are achieved.

CN119528557APending Publication Date: 2025-02-28NORTHWESTERN POLYTECHNICAL UNIV

Patent Information

Application Number
CN202411715574.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing alumina fiber reinforced ceramic matrix composites have shortcomings in thermal insulation properties and lack effective reinforcement methods.

Method used

The preparation method of alumina fiber-reinforced mullite ceramic matrix composite material with a ceramic matrix concentration from inside to outside is adopted. By introducing a structure with a volume concentration gradient distribution into the material, the surface layer forms a dense structure and a porous structure is formed in the center, thereby improving the thermal insulation performance.

Benefits of technology

On the premise of ensuring mechanical properties, the thermal insulation performance of alumina fiber reinforced mullite ceramic matrix composites is significantly improved, lightweight and high-strength characteristics are achieved, and excellent damage resistance under dynamic stress environments.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses an alumina fiber reinforced mullite ceramic-based composite material with volume concentration gradient distribution, which is composed of continuous alumina fiber cloth and a mullite ceramic matrix, the continuous alumina fiber cloth and the mullite ceramic matrix are in volume concentration gradient distribution, the volume density of the alumina fiber at the center is 50-60%, and the volume density of the alumina fiber at the center is 50-60%. The volume density of the mullite ceramic is 10-20%, the volume densities of the alumina fiber and the mullite ceramic are gradually increased from the center to the outside, the volume density of the surface alumina fiber is 70-80%, the volume density of the mullite ceramic is 20-30%, and the surface alumina fiber and the mullite ceramic form a compact structure which can block air conduction. The heat insulation performance of the alumina fiber reinforced mullite ceramic-based composite material is remarkably improved, and the high-strength characteristic is achieved while the light weight is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fiber-reinforced ceramic-based composite materials, and in particular to an alumina fiber-reinforced ceramic-based composite material with a volume concentration gradient and a preparation method thereof. Technical Background

[0002] Continuous alumina fiber reinforced ceramic matrix composites have excellent high temperature resistance, oxidation resistance, good mechanical properties and thermal insulation properties, and have broad application prospects in the fields of aviation, aerospace, nuclear energy, etc. The vacuum impregnation, drying, and heat treatment molding process is adopted on the three-dimensional fabric. Alumina fibers are usually woven into fiber preforms, and then impregnated, dried, densified, and then subjected to high-temperature heat treatment to finally obtain reinforced ceramic matrix composites.

[0003] Zhang Ke, Xu Ping, Zhang Chao, et al. Domestic Al2O 3f Room temperature and 1000℃ tensile properties of / Al2O3 composites[J]. Materials Engineering. 3f / Al2O3 composite materials were tested for room temperature and 1000℃ tensile mechanical properties. The results show that domestic Al2O 3f The tensile strength of / Al2O3 composite materials has reached the level of foreign Nextel610 / Al2O3. Interface bonding strength is the main factor affecting tensile strength. If the interface bonding strength is low, the fiber pullout is long and dispersed, and the tensile strength is high. If the interface bonding strength is high, the fiber bundle breaks, the fiber pullout becomes shorter, and the tensile strength is low. This paper shows that the domestic Al2O 3f / Al2O3 composite material raw materials are not inferior to those abroad, but how to make Al2O3 3f / Al2O3 composites were not mentioned.

[0004] Zhong Wenli, Liu Yichang, Qin Gaolei, et al. Preparation and performance research of alumina fiber reinforced ceramic matrix wave-transmitting composite materials containing LaPO4 interface phase [J]. Journal of Air Force Engineering University. Alumina fiber reinforced ceramic matrix composite materials were prepared with alumina fiber as reinforcement, alumina slurry and mullite sol as matrix, and lanthanum phosphate as interface layer material. The tensile strength of the composite materials at room temperature and 1200℃ was characterized, and the failure law was observed by scanning electron microscopy. The results show that the tensile strength of the composite materials introduced with LaPO4 interface phase at room temperature is 20.1% and 24.9% higher than that of the composite materials without interface phase, respectively. The fracture of alumina fiber reinforced ceramic matrix composite materials without interface phase is flat, showing brittle fracture. The fracture of alumina fiber reinforced ceramic matrix composite materials with LaPO4 interface phase has a large number of fibers pulled out, showing ductile fracture characteristics. This article explains the LaPO4 interface relative to Al2O 3f / Al2O3 composite materials have a good effect on improving mechanical properties, but the preparation method lacks innovation and does not pay attention to the thermal insulation properties of the composite materials.

[0005] Application No. CN114409420A discloses an alumina fiber reinforced mullite ceramic matrix composite material and a preparation method thereof, which relates to the technical field of fiber reinforced ceramic composite materials. The preparation steps of the method include: preparing mullite sol by ball milling; pretreatment of alumina fiber cloth; preparation of lanthanum phosphate interface layer; vacuum-hot pressing molding and densification, and finally obtaining a finished product of alumina fiber reinforced mullite ceramic matrix composite material. This method uses alumina fiber as a reinforcing phase to enhance the strength of the alumina matrix, the preparation process is simple, and the prepared finished product has excellent high-temperature mechanical properties. The alumina fiber reinforced mullite ceramic matrix composite material provided by this invention is a lanthanum phosphate interface layer prepared on the surface of the alumina fiber, which can effectively improve the strong bond between the fiber and the matrix. Secondly, mullite powder and mullite sol are mixed and ball milled to prepare mullite sol, mullite powder particles with low sintering activity are used as fillers, and mullite sol particles with high sintering activity are used as binders, which can improve the impregnation efficiency while maintaining the sintering activity of the matrix. Finally, the composite material provided by this invention has excellent high-temperature mechanical properties, and its preparation method is simple, low-cost and short-cycle, but it does not pay attention to the thermal insulation performance of the composite material.

[0006] Application number CN116375486A relates to a method for preparing alumina fiber reinforced alumina ceramic matrix composite material quickly and at low cost. The method comprises: pre-treating an alumina fiber preform to remove the impregnant; preparing a lanthanum phosphate interface slurry; vacuum impregnating the pre-treated alumina fiber preform in the lanthanum phosphate interface slurry, and then drying and sintering to obtain a preform containing a lanthanum phosphate interface layer; preparing an alumina slurry; vacuum impregnating the preform containing the lanthanum phosphate interface layer in the alumina slurry, and then drying to obtain a sheet prepreg; preparing an alumina raw sheet by tape casting the alumina slurry; arranging the alumina raw sheet and the sheet prepreg alternately in a mold, and then sintering to obtain an alumina fiber reinforced alumina ceramic matrix composite material. This invention can realize the short-cycle and low-cost preparation of high-performance continuous alumina fiber reinforced alumina composite material, which is of great significance to the industrialization of the material, but it also does not pay attention to the thermal insulation performance of the composite material.

[0007] Application No. CN115196984A relates to a continuous alumina fiber reinforced oxide ceramic matrix composite material modified by a three-dimensional woven interface and a preparation method thereof. The preparation method of the present invention comprises the following steps: firstly, a three-dimensional structure alumina fiber preform composited with oxide powder is woven; using polyzirconium yttrium oxide as a precursor solution, a precursor impregnation pyrolysis method is adopted to obtain an yttria-stabilized zirconia (YSZ) interface; using an oxide organic polymer as a precursor solution, a precursor impregnation pyrolysis method is adopted again to composite the oxide matrix, and an alumina fiber reinforced oxide ceramic matrix composite material containing a YSZ weak interface is obtained by high-temperature sintering. The YSZ weak interface significantly improves the strength, fracture toughness and damage tolerance of the composite material. The precursor impregnation pyrolysis method adopted in this invention can greatly avoid fiber corrosion and high-temperature damage, and can achieve net size molding to obtain a high-density matrix. However, the invention lacks a specific description of its performance advantages, and does not mention the thermal insulation performance.

[0008] Application No. CN118164772A provides a high-density preparation of alumina fiber reinforced alumina ceramic matrix composite material and a low-temperature preparation method thereof. The method comprises pre-treating an alumina fiber preform to remove glue; preparing a lanthanum phosphate interface solution, fully soaking the pre-treated alumina fiber preform in the lanthanum phosphate interface solution for vacuum impregnation, taking it out and standing it for low-temperature drying, low-temperature pre-sintering, and cycling it for multiple times until the interface layer reaches a set thickness, thereby obtaining a preform containing a lanthanum phosphate interface layer; preparing an aluminum sol containing lithium fluoride, vacuum impregnating the preform containing a lanthanum phosphate interface layer in the aluminum sol containing lithium fluoride, taking it out and standing it for low-temperature drying, low-temperature pre-sintering, cycling it for multiple times until the weight gain is less than 1wt%, and performing normal pressure sintering in an air atmosphere to obtain an alumina fiber reinforced alumina ceramic matrix composite material containing a lanthanum phosphate interface layer. This invention ensures that the material obtains a high-performance continuous alumina fiber reinforced alumina composite material with high crystallinity, high density, low porosity and low fiber damage at a relatively low sintering temperature by uniformly adding lithium fluoride to the alumina matrix. It reduces the sintering and densification temperature of the alumina matrix, avoids the loss of oxidized fibers due to high-temperature sintering, improves the mechanical properties of the composite material, and increases the application potential of the material in actual production. However, it also does not pay attention to the thermal insulation performance of the composite material.

[0009] Application No. CN118005383A discloses a method for preparing an alumina fiber reinforced alumina-based composite material, which comprises: mixing a resin, a dispersant, a sintering aid and an alumina powder in proportion and then ball milling to obtain an alumina slurry; vacuum impregnating the degummed alumina woven piece with the degassed alumina slurry; after the impregnation, placing it in a compression mold, applying a certain pressure, and then releasing the pressure; then performing a high-temperature treatment together with the compression mold, removing the mold after cooling, repeating the vacuum impregnation and high-temperature treatment until the weight gain rate of the alumina woven piece is reduced to less than 1%, and obtaining a composite material rough blank; vacuum impregnating the rough blank with alumina sol; drying and high-temperature treatment of the impregnated rough blank, and cooling naturally; repeating vacuum impregnation-drying-high-temperature treatment until the weight gain rate of the rough blank is reduced to less than 1%, and obtaining a composite material. This method can achieve the preparation of high-performance composite materials in a shorter period. This method shortens the preparation cycle of the composite material, but it also does not pay attention to the thermal insulation performance of the composite material, and there is no performance improvement compared to other products.

[0010] The above inventions are of great value in improving the preparation speed and mechanical properties of fiber-reinforced ceramic-based composite materials, but lack attention and improvement on thermal insulation performance.

[0011] Application No. CN117264144A relates to a porous structure CNTs / Si-OC composite material with high strength and ultra-low thermal conductivity and a preparation method thereof, the method comprising: mixing trivinylsilane and mercaptopropionate to obtain a first mixed solution; adding CNTs to the first mixed solution and mixing to obtain a second mixed solution; adding a photoinitiator to the second mixed solution and mixing to obtain a CNTs-modified Si-OC precursor; 3D printing with the CNTs-modified Si-OC precursor as a raw material based on a porous structure model and sintering in an inert atmosphere to obtain a porous structure CNTs / Si-OC composite material with ultra-low thermal conductivity. However, compared with alumina fiber reinforced alumina-based composite materials, its mechanical properties are poor.

[0012] Application No. CN117510228A relates to a ceramic-hybrid resin-based gradient heat-insulating integrated composite material and a preparation method thereof, comprising the following steps: selecting an organosilicon hybrid resin as a matrix raw material, adding a pore-forming solvent, and selecting a fiber preform of a silicon carbide-quartz gradient woven structure as a reinforcement; injecting resin into the fiber preform through an alternating vacuum-assisted RTM process, and curing the injected resin through an alternating temperature curing process to obtain a porous resin-based composite material; impregnating a silicon-containing ceramic precursor from the silicon carbide fiber side of the porous resin-based composite material through alternating pressure impregnation to form a gradient structure with high surface content and low internal content, and fully curing to obtain a gradient resin-based composite material; heating the silicon carbide fiber side of the gradient resin-based composite material. The material can achieve multiple functions such as ablation resistance and long-term heat insulation, and can be applied to thermal protection materials for aerospace vehicles. However, compared with alumina fiber-reinforced ceramic-based composite materials, it only has outstanding high temperature resistance on the silicon carbide fiber side.

[0013] It can be seen from these patents that for fiber-reinforced ceramic-based composite materials, there have been fruitful and systematic research results in shortening the preparation cycle, improving density, improving mechanical properties, and reducing costs, but the means of increasing its thermal insulation properties are still lacking. As for resin-based composite materials with excellent thermal insulation properties, they often have a multilayer structure, but only have outstanding high temperature resistance on the silicon carbide fiber side, and the mechanical properties are lower than those of fiber-reinforced ceramic-based composite materials. To this end, the present invention provides a method for preparing an alumina fiber reinforced mullite ceramic-based composite material with a ceramic matrix concentration from small to large from the inside to the outside, the purpose of which is to enhance the thermal insulation properties of alumina fiber composite ceramics while ensuring the mechanical properties as much as possible. Summary of the invention

[0014] In order to solve the defects or shortcomings in the prior art, the purpose of the present invention is to provide an alumina fiber reinforced mullite ceramic matrix composite material and a preparation method thereof in which the ceramic matrix concentration increases from small to large from the inside to the outside, while ensuring the mechanical properties as much as possible, so as to enhance the thermal insulation properties of the alumina fiber reinforced mullite ceramic matrix composite material.

[0015] The technical solution adopted to achieve the purpose of the patent of the present invention is: an alumina fiber reinforced mullite ceramic-based composite material with a volume concentration gradient distribution, which is composed of a continuous alumina fiber cloth and a mullite ceramic matrix, characterized in that the continuous alumina fiber cloth is distributed in a volume concentration gradient, the volume density of the alumina fiber at the center is 50-60%, the volume density of the alumina fiber gradually increases from the center to the outside, and the volume density of the surface alumina fiber is 70-80%; the mullite ceramic matrix is ​​distributed in a volume concentration gradient, the volume density of the mullite ceramic at the center is 10-20%, the volume density of the mullite ceramic gradually increases from the center to the outside, and the volume density of the surface mullite ceramic is 20-30%; the surface alumina fiber and mullite ceramic form a dense structure, and a porous structure is formed at the center, thereby achieving a synergistic improvement in mechanical properties and thermal insulation properties.

[0016] Furthermore, the method for preparing the alumina fiber reinforced mullite ceramic matrix composite material with a volume concentration gradient is characterized by comprising the following steps:

[0017] 1) placing the continuous alumina fiber in a muffle furnace for heating treatment at a temperature of 500-600° C., removing the impregnant on the surface of the continuous alumina fiber cloth, and taking it out after natural cooling to obtain the continuous alumina fiber cloth with the impregnant removed;

[0018] 2) 0.1-1.0 mol / L lanthanum nitrate and phosphoric acid of the same molar concentration are mixed at 0-5° C. to obtain a lanthanum phosphate precursor solution, and then the continuous alumina fiber cloth is vacuum immersed in the lanthanum phosphate precursor solution for reaction, and then taken out and washed with ultrapure water for 1-3 times, and then placed in an oven for drying at a temperature of 90-120° C. and a drying time of 1-2 hours, and finally heat-treated in a muffle furnace at a temperature of 700-900° C. and a heat treatment time of 1-3 hours to obtain an alumina fiber cloth and a continuous alumina fiber containing a lanthanum phosphate interface layer;

[0019] 3) Alumina powder and mullite sol are mixed in a mass ratio of (1-5): (2-10) to obtain an alumina / mullite sol slurry, and then the laid continuous alumina fiber cloth is immersed in the alumina / mullite sol slurry, fully impregnated under negative pressure, and then placed between two flat molds, clamped by pressure from top to bottom, and the clamped mold is placed in an oven for gradient drying, the first drying temperature is 90-100° C., the drying time is 1-2 hours, the second drying temperature is 120-130° C., the drying time is 0.5-1 hour, and the third drying temperature is 200-300° C., and the time is 2-4 hours, to obtain an alumina fiber reinforced mullite ceramic matrix composite body;

[0020] 4) removing the mold, placing the alumina fiber reinforced mullite ceramic-based composite body in a muffle furnace for sintering in an air atmosphere, the sintering temperature is 600-1200°C, the sintering time is 1-3h, to obtain an alumina fiber reinforced mullite ceramic-based composite material, and then immersing it in an alumina / mullite sol slurry, impregnating it for a short time at normal pressure, and sintering it in a nitrogen atmosphere after drying, the sintering temperature is 600-1200°C, the sintering time is 1-3h, repeating the above process 4-6 times, to obtain an alumina fiber reinforced mullite ceramic-based composite material with a volume concentration gradient distribution.

[0021] The beneficial effects of the present invention are:

[0022] ① The present invention first immerses continuous alumina fiber cloth into alumina / mullite sol slurry for full impregnation under negative pressure, and then sintering is carried out in an air atmosphere. The obtained alumina fiber reinforced mullite ceramic-based composite material has a porous structure, and then it is briefly immersed in the alumina / mullite sol slurry at normal pressure to obtain an alumina fiber reinforced mullite ceramic-based composite material with a volume concentration gradient distribution. The surface alumina fibers and mullite ceramics form a dense structure that can block the conduction of air, thereby significantly improving the thermal insulation performance of the alumina fiber reinforced mullite ceramic-based composite material.

[0023] ② The present invention prepares an alumina fiber reinforced mullite ceramic-based composite material with a volume concentration gradient, wherein the volume density of the alumina fiber at the center is 50-60%, and the volume density of the mullite ceramic is 10-20%, and the volume density of the alumina fiber and the mullite ceramic gradually increases from the center to the outside, the volume density of the surface alumina fiber is 70-80%, and the volume density of the mullite ceramic is 20-30%, and the surface alumina fiber and the mullite ceramic form a dense structure, achieving light weight and high strength characteristics.

[0024] ③ The present invention prepares a lanthanum phosphate interface layer on the surface of alumina fiber, forming a weak interface layer with low toughness between the fiber and the matrix. In addition, the lanthanum phosphate interface layer also promotes the pull-out behavior of the fiber during crack propagation by reducing the slip stress between the fiber and the matrix. Combined with the volume concentration gradient distribution structure, the alumina fiber reinforced mullite ceramic matrix composite material prevents the brittle failure of the material in the early stage of crack development, has excellent damage resistance under dynamic stress environment, and can effectively prevent the uncontrolled propagation of cracks. DETAILED DESCRIPTION

[0025] The technical solutions in the embodiments of the present invention will be described clearly and completely below in combination with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] Example

[0027] The invention discloses an alumina fiber reinforced mullite ceramic-based composite material with a volume concentration gradient distribution, which is composed of a continuous alumina fiber cloth and a mullite ceramic matrix. The invention is characterized in that the continuous alumina fiber cloth is distributed in a volume concentration gradient, the volume density of the alumina fiber at the center is 50%, the volume density of the alumina fiber gradually increases from the center to the outside, and the volume density of the surface alumina fiber is 80%; the mullite ceramic matrix is ​​distributed in a volume concentration gradient, the volume density of the mullite ceramic at the center is 10%, the volume density of the mullite ceramic gradually increases from the center to the outside, and the volume density of the surface mullite ceramic is 20%; the surface alumina fiber and the mullite ceramic form a dense structure, and the center forms a porous structure, thereby realizing the synergistic improvement of mechanical properties and thermal insulation properties.

[0028] Furthermore, the method for preparing the alumina fiber reinforced mullite ceramic matrix composite material with a volume concentration gradient is characterized by comprising the following steps:

[0029] 1) placing the continuous alumina fiber in a muffle furnace for heating treatment at a temperature of 600° C. to remove the impregnant on the surface of the continuous alumina fiber cloth, and taking it out after natural cooling to obtain the continuous alumina fiber cloth with the impregnant removed;

[0030] 2) 0.50 mol / L lanthanum nitrate and phosphoric acid of the same molar concentration were mixed at 5°C to obtain a lanthanum phosphate precursor solution, and then the continuous alumina fiber cloth was vacuum immersed in the lanthanum phosphate precursor solution for reaction, and then taken out and washed with ultrapure water for 3 times, and then placed in an oven for drying at a drying temperature of 100°C and a drying time of 1.5 h, and finally heat-treated in a muffle furnace at a heat treatment temperature of 800°C and a heat treatment time of 2 h to obtain an alumina fiber cloth and a continuous alumina fiber containing a lanthanum phosphate interface layer;

[0031] 3) Alumina powder and mullite sol are mixed in a mass ratio of 5:10 to obtain an alumina / mullite sol slurry, and then the continuous alumina fiber cloth after layering is immersed in the alumina / mullite sol slurry, fully impregnated under negative pressure, and then placed between two flat molds, clamped by pressure from top to bottom, and the clamped mold is placed in an oven for gradient drying, the first drying temperature is 100°C, the drying time is 1h, the second drying temperature is 120°C, the drying time is 0.1h, and the third drying temperature is 250°C, the time is 2h, to obtain an alumina fiber reinforced mullite ceramic matrix composite body;

[0032] 4) Remove the mold, place the alumina fiber reinforced mullite ceramic-based composite material body in a muffle furnace and sinter it in an air atmosphere at a sintering temperature of 800°C for 2 hours to obtain an alumina fiber reinforced mullite ceramic-based composite material, and then immerse it in alumina / mullite sol slurry, impregnate it for a short time at normal pressure, and after drying, sinter it in a nitrogen atmosphere at a sintering temperature of 1000°C for 2 hours. Repeat the above process 5 times to obtain an alumina fiber reinforced mullite ceramic-based composite material with a volume concentration gradient distribution.

[0033] The above is only a specific implementation of the present invention, but the design concept of the present invention is not limited to this. Any non-substantial changes to the present invention using this concept shall be deemed as an act that infringes the scope of protection of the present invention. However, any simple modification, equivalent change and modification made to the above embodiment in any form according to the technical essence of the present invention without departing from the content of the technical solution of the present invention shall still fall within the scope of protection of the technical solution of the present invention.

Claims

1. An alumina fiber reinforced mullite ceramic matrix composite material with a volume concentration gradient distribution, consisting of a continuous alumina fiber cloth and a mullite ceramic matrix, characterized in that The continuous alumina fiber cloth is distributed in a volume concentration gradient, the volume density of the alumina fiber at the center is 50-60%, the volume density of the alumina fiber gradually increases from the center to the outside, and the volume density of the surface alumina fiber is 70-80%; the mullite ceramic matrix is ​​distributed in a volume concentration gradient, the volume density of the mullite ceramic at the center is 10-20%, the volume density of the mullite ceramic gradually increases from the center to the outside, and the volume density of the surface mullite ceramic is 20-30%; the surface alumina fiber and mullite ceramic form a dense structure, and a porous structure is formed in the center, thereby achieving a synergistic improvement in mechanical properties and thermal insulation properties.

2. A method for preparing the alumina fiber reinforced mullite ceramic matrix composite material with volume concentration gradient according to claim 1, characterized in that The following steps are involved: 1) placing the continuous alumina fiber in a muffle furnace for heating treatment at a temperature of 500-600° C., removing the impregnant on the surface of the continuous alumina fiber cloth, and taking it out after natural cooling to obtain the continuous alumina fiber cloth with the impregnant removed; 2) 0.1-1.0 mol / L lanthanum nitrate and phosphoric acid of the same molar concentration are mixed at 0-5° C. to obtain a lanthanum phosphate precursor solution, and then the continuous alumina fiber cloth is vacuum immersed in the lanthanum phosphate precursor solution for reaction, and then taken out and washed with ultrapure water for 1-3 times, and then placed in an oven for drying at a temperature of 90-120° C. and a drying time of 1-2 hours, and finally heat-treated in a muffle furnace at a temperature of 700-900° C. and a heat treatment time of 1-3 hours to obtain an alumina fiber cloth and a continuous alumina fiber containing a lanthanum phosphate interface layer; 3) Alumina powder and mullite sol are mixed in a mass ratio of (1-5): (2-10) to obtain an alumina / mullite sol slurry, and then the laid continuous alumina fiber cloth is immersed in the alumina / mullite sol slurry, fully impregnated under negative pressure, and then placed between two flat molds, clamped by pressure from top to bottom, and the clamped mold is placed in an oven for gradient drying, the first drying temperature is 90-100° C., the drying time is 1-2 hours, the second drying temperature is 120-130° C., the drying time is 0.5-1 hour, and the third drying temperature is 200-300° C., and the time is 2-4 hours, to obtain an alumina fiber reinforced mullite ceramic matrix composite body; 4) removing the mold, placing the alumina fiber reinforced mullite ceramic-based composite body in a muffle furnace for sintering in an air atmosphere, the sintering temperature is 600-1200°C, the sintering time is 1-3h, to obtain an alumina fiber reinforced mullite ceramic-based composite material, and then immersing it in an alumina / mullite sol slurry, impregnating it for a short time at normal pressure, and sintering it in a nitrogen atmosphere after drying, the sintering temperature is 600-1200°C, the sintering time is 1-3h, repeating the above process 4-6 times, to obtain an alumina fiber reinforced mullite ceramic-based composite material with a volume concentration gradient distribution.

Citation Information

Patent Citations

  • Three-dimensional woven interface phase-containing alumina fiber reinforced oxide ceramic-based composite material and preparation method thereof

    CN115196984A

  • Method for rapidly preparing alumina fiber reinforced alumina ceramic-based composite material at low cost

    CN116375486A

  • Porous-structure CNTs / Si-O-C composite material with high strength and ultralow thermal conductivity and preparation method of porous-structure CNTs / Si-O-C composite material

    CN117264144A

  • Ceramic-hybrid resin based gradient heat prevention and insulation integrated composite material and preparation method thereof

    CN117510228A

Cited By

  • Mullite heat-insulating brick and preparation method thereof

    CN119977542A

  • Heat-insulating and wave-absorbing skin material as well as preparation method and application thereof

    CN121403770A

  • Continuous mullite fiber strengthened and toughened mullite-alumina-based composite material with high mechanical property and high thermal stability and preparation method of continuous mullite fiber strengthened and toughened mullite-alumina-based composite material

    CN122102663A

  • Mullite ceramic fiber and preparation method and application thereof

    CN122856402A